Towards defining the role of translation regulation during viral infection in plants. - Sans-Coll, Gemma; Castillo-Garriga, Araceli; Rodríguez-Bejarano, Eduardo; Merchante-Berg, Catharina (My University, 2024)
Tomato yellow leaf curl virus (TYLCV) is responsible for massive damage to tomato crops worldwide (Prasad et al., 2020). Due to its viral nature, it requires the host’s cellular machinery to be able to infect, which implies complex interactions between the virus and the plant. Most studies about this association are based on transcriptomics and interactomics, while translatomics analyses have, so far, been scarce. Understanding the translational mechanisms responsible for the production of viral proteins and, consequently, its propagation will allow to shed some light on these interactions and gain knowledge about the changes at the translational level that tomato plants experience upon infection. To that end, we are characterizing the translational landscape of the plant-virus interaction using RNA-seq of polysomal RNA. To deepen our knowledge of the regulatory mechanisms involved in the translational response, two isogenic tomato lines, one resistant (the ty-5 mutant) and one susceptible (Santa Clara) to TYLCV are being employed. Ty-5 is a recessive mutation located on the Pelota gene, which is involved in the recycling phase of the translation cycle (Lapidot et al., 2015), so the study of this mutant will inform about the role of the translational machinery in the viral infection. In addition, using RIP+MS, we are attempting to uncover the translational machinery associated with viral transcripts to determine if certain riboproteins or translation factors are preferred for translating viral transcripts. We will present the advances we have made regarding these objectives. References Lapidot et al. PLoS Genet. 11:e1005538. Prasad et al. Trends Plant Sci 2020 Sep;25(9):897-911. Acknowledgments: The authors are grateful to Rafael Fernández-Muñoz (IHSM) for sharing the ty-5 and Santa Clara tomato seeds. This work is funded by Grant P18-RT-1218 from the Junta de Andalucía to CM and ERB, and grants RYC2017-22323 and PID2021-12324NB-100 to CM.
Keywords: Tomates - Enfermedades y plagas; Virus fitopatógenos; Virus; Tomate; Traducción